Möhlig & Kavari 2008. Reference Grammar of Herero (Otjiherero) - Lusekelo, Amani (AAeO - Afrikanistik-Aegyptologie-Online, 2009)
Wilhelm J.G. Möhlig & Jekura U. Kavari 2008. Reference Grammar of Herero (Otjiherero). Bantu Languages of Namibia. With a Glossary Otjiherero-English-Otjiherero. Southern African Languages and Cultures, Vol. 3. Rüdiger Köppe Verlag, Köln. 372 pages; 5 Parts – including Glossary and Texts; 12 Chapters; Several Tables and Illustrations; 1 map; Index